2023
DOI: 10.3390/molecules28020789
|View full text |Cite
|
Sign up to set email alerts
|

An Exemestane Derivative, Oxymestane-D1, as a New Multi-Target Steroidal Aromatase Inhibitor for Estrogen Receptor-Positive (ER+) Breast Cancer: Effects on Sensitive and Resistant Cell Lines

Abstract: Around 70–85% of all breast cancer (BC) cases are estrogen receptor-positive (ER+). The third generation of aromatase inhibitors (AIs) is the first-line treatment option for these tumors. Despite their therapeutic success, they induce several side effects and resistance, which limits their efficacy. Thus, it is crucial to search for novel, safe and more effective anti-cancer molecules. Currently, multi-target drugs are emerging, as they present higher efficacy and lower toxicity in comparison to standard optio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 68 publications
1
4
1
Order By: Relevance
“…In relation to aromatase, results showed that in the presence of E 2 , G significantly lost the ability to decrease MCF-7aro cell viability (Figure 4A) when compared with cells stimulated with T, which suggests an effect on cells that is aromatase-dependent. In accordance with previous studies [11,14,[34][35][36][37][38], Exe decreases the aromatase levels in MCF-7aro cells. Similarly to Exe, G at 10 µM was also able to significantly (p < 0.001) reduce the expression levels of aromatase (Figure 4B).…”
Section: Genistein Affects Aromatase and Hormone Receptors' Expressionssupporting
confidence: 93%
See 1 more Smart Citation
“…In relation to aromatase, results showed that in the presence of E 2 , G significantly lost the ability to decrease MCF-7aro cell viability (Figure 4A) when compared with cells stimulated with T, which suggests an effect on cells that is aromatase-dependent. In accordance with previous studies [11,14,[34][35][36][37][38], Exe decreases the aromatase levels in MCF-7aro cells. Similarly to Exe, G at 10 µM was also able to significantly (p < 0.001) reduce the expression levels of aromatase (Figure 4B).…”
Section: Genistein Affects Aromatase and Hormone Receptors' Expressionssupporting
confidence: 93%
“…We have previously demonstrated that G decreases aromatase activity in human placental microsomes [ 29 ]. In addition, this study showed for the first time that G presents an aromatase-dependent effect on ER+ breast cancer cells, since G, at 10 µM, has the ability to decrease the expression levels of aromatase in MCF-7aro cells, an effect similar to Exe [ 11 , 14 , 34 , 35 , 36 , 37 , 38 ] and opposite to those already reported for Ana and Let [ 14 ]. Interestingly, only the combination with G at 10 µM prevented the degradation of aromatase detected for both G and Exe alone, which emphasizes that the loss of clinical benefit for the highest dose of G may be related to the lack of effect on aromatase.…”
Section: Discussioncontrasting
confidence: 70%
“…The tests showed that derivative 6 reduced the expression and activation of ERα and induced the overexpression of aromatase with an effect promoting cell death. Complementary transactivation assays showed that molecule 6 exhibited ER antagonist and AR agonist activity [ 15 ].…”
Section: Aromatase Inhibitorsmentioning
confidence: 99%
“…In 2012, Lu et al [ 11 ] reported the first evidence of the ability of a single compound to interact with significant activities on two targets involved in the progression of ER+ BC. This discovery paved the way for the identification of new multitarget compounds capable of overcoming the limitations of current therapeutic strategies [ 12 ]; different series of compounds have been recently developed and/or evaluated for their multipotent activity [ 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%